2021
DOI: 10.1002/lno.11794
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate fluxes induced by turbulent mixing in dipole eddies in an oligotrophic ocean

Abstract: The vertical turbulent fluxes of nitrate to the base of the euphotic zone were quantified to assess the role of turbulent mixing in modulating new production inside cyclonic and anticyclonic eddies in an oligotrophic ocean. Although the turbulent nitrate flux (0.35 AE 0.11 mmol N m À2 d À1 ) at the base of the euphotic zone inside the cyclonic eddy was higher than that (0.07 AE 0.03 mmol N m À2 d À1 ) inside the anticyclonic eddy, this flux contributed to 19.7-76.3% of new production in the anticyclonic eddy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In the dipole eddies in western South China Sea, Li et al. (2021) quantified the vertical nitrate fluxes to the base of the euphotic zone in the same cruise and found that the turbulent nitrate flux at the base of the euphotic zone of CE was significantly higher than that of ACE and the new production in CE was mainly supported by upwelling. Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the dipole eddies in western South China Sea, Li et al. (2021) quantified the vertical nitrate fluxes to the base of the euphotic zone in the same cruise and found that the turbulent nitrate flux at the base of the euphotic zone of CE was significantly higher than that of ACE and the new production in CE was mainly supported by upwelling. Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The most common manifestations of mesoscale eddies regulating the rates of biological processes are related to vertical movements which can affect the availability of both light and nutrients to phytoplankton and thereby alter the growth of phytoplankton (Cullen, 2015; Li et al., 2021). Mesoscale eddies affect phytoplankton distribution and hence Chl concentrations via different mechanisms, such as nutrient pumping associated with eddy intensification (Falkowski et al., 1991; McGillicuddy, 2016), diapycnal nutrient fluxes as a result of the steeper vertical gradients in inorganic nutrients caused by eddies (Barone et al., 2022) and the redistribution of nutrients in the euphotic zone due to eddy‐induced vertical oscillations of the pycnocline (Falkowski et al., 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Turbulence and shear enhance encounter rates of TEP precursor and coagulation of particles increasing their sizes (Beauvais et al, 2006;Pedrotti et al, 2010;Burns et al, 2019). Floating particles tend to gather in CEs's core due to horizontal shear instabilities promoting shear and spirals (Munk et al, 2000) and turbulence kinetics are higher at the center of the CEs due to upwelling (Li et al, 2021). Simultaneously, though, it is also expected that the increased frequency of collisions will facilitate more collisions amongst larger aggregates.…”
Section: Transparent Exopolymer Particles (Tep)mentioning
confidence: 99%